Preoperational cleaning processes interfere with microbial ecology and presence of Listeria monocytogenes and Salmonella spp. on food conveyor belts of a poultry slaughterhouse in Brazil - Ereno Tadielo, Leonardo [UNESP]; Aparecida Rodrigues dos Santos, Emanoelli [UNESP]; Sossai Possebon, Fábio [UNESP]; Arruda Schmiedt, Jhennifer; Henrique Silva Orisio, Paulo; Bastos Juliano, Lara Cristina [UNESP]; Koutsodontis Cerqueira-Cézar, Camila [UNESP]; Paes de Almeida Nogueira Pinto, José [UNESP]; Gonçalves Pereira, Juliano [UNESP]; Bersot, Luciano dos Santos (Elsevier, 2023)
This study aimed to evaluate the preoperational cleaning process of a poultry slaughterhouse regarding microbial ecology, microorganisms indicators of hygienic-sanitary conditions, Listeria monocytogenes and Salmonella spp. Three hundred and twenty samples were collected from the surfaces of meat cut conveyor belts before (n = 160) and after (n = 160) the preoperational cleaning process to count mesophilic aerobes, Enterobacteriaceae, and Pseudomonas spp., in addition to the detection of L. monocytogenes and Salmonella spp., and identification of microbial ecology by sequencing the 16S rRNA gene. The hygiene process reduced the counts of all the indicator microorganisms (87% a 91%) and eliminated Salmonella spp. Despite this significant decrease, L. monocytogenes persisted on some of the conveyor belts. Microorganisms associated with obtaining and handling meat cuts, including Aneurinibacillus, Anoxybacillus, Enterococcus, and Pseudomonas, were used to characterize the microbial ecology before cleaning. A disturbance in microbial ecology was identified post-cleaning, in which microorganisms with greater adaptation and tolerance to industrial conditions, such as Pseudomonas, Acinetobacter, and Aeromonas, were more prevalent. Our results revealed that the cleaning and sanitization procedures were effective in reducing the levels of indicator microorganisms and Salmonella spp. The applied hygiene process also shaped the composition of the existing microbial ecology.
Keywords: Cleaning; Conveyor belt surfaces; Food industry; Microbiota; Pathogen occurrence